Phase stability and phase transformations in Al-Pd-Mn quasicrystalline alloys with low-Ga content - Mishra S.S.; Yadav T.P.; Mukhopadhyay N.K. (My University, 2025)
Gallium having low surface energy (∼ 600 mJ/m2) and low melting temperature (29.76 °C), was utilized to substitute Al in Al-Pd-Mn quasicrystalline alloys, which may be considered for future development of a quaternary QC alloy with low surface energy. The influence of Ga up to 5 at% in decagonal Al70-XGaXPd10Mn20 (x = 0, 2.5, 5.0) alloys on the stability of decagonal phase was investigated systematically. The surface morphology and phase stability were studied in as-cast (slow cooling from liquid) and also in annealed condition (i.e., annealing at temperature 800 °C for 24 h). It is observed that Ga influences the stability of decagonal phase and the evolution of microstructure. The phase transformation from the mixed icosahedral and decagonal quasicrystal phases coexisting in as-cast Al70-XGaXPd10Mn20 (x = 0, 2.5, 5.0) alloys to a single decagonal quasicrystalline phase was observed on annealing, implying relative phase stability of quaternary decagonal phase around these compositions. © 2021